Colloidosomes as a Protocell Model: Engineering Life‐Like Behaviour through Organic Chemistry. Issue 43 (14th November 2022) - Park, Jun Hyeong; Galanti, Agostino; Ayling, India; Rochat, Sebastien; Workentin, Mark S.; Gobbo, Pierangelo
Abstract: The bottom‐up synthesis of self‐assembled micro‐compartmentalised systems that mimic basic characteristics of living cells is rapidly evolving. These types of systems are termed "protocells" and can be chemically programmed to grow and divide, to send and receive chemical signals, to transcript and translate chemical information, to adhere to surfaces or to other protocells, and to perform rudimental enzyme‐mediated metabolic processes. An emerging protocell model that is attracting great attention is the colloidosome. Colloidosomes are microcapsules with a chemically crosslinked, semipermeable membrane composed of amphiphilic nanoparticles. Colloidosomes display important advantages over other protocell models (e. g., vesicles and coacervate micro‐droplets) due to their physical‐chemical properties that can be easily tuned through the careful engineering of their synthetic building blocks. In this review, we deliver an overview of the different types of colloidosomes that have been developed thus far and discuss how organic chemistry contributes to the design and bottom‐up synthesis of novel types of colloidosomes endowed with advanced chemically programmed bio‐inspired functions. Abstract : Colloidosomes are robust, versatile microcapsules that have emerged as promising candidates for protocell models. With the help of synthetic organic chemistry, colloidosome protocells have been engineered to mimic a plethora of biotic cell behaviours, including membrane permeability, multi‐compartmentalisation, replication, signalling, and predatory behaviour. Networks of interconnected colloidosomes have also been fabricated to mimic biological tissues.